A study of occupational health among mine workers in Murmansk Oblast, Russia - Skandfer, Morten (2014)
The mining industry is growing in the north, with the largest mining communities located in North Russia. Increased knowledge about the health and work conditions of the employees is important in order to enhance safety and prevention of ill health. The aim of the study was to describe how the health of mine workers in Murmansk oblast is assessed, determine the prevalence of low back pain (LBP) as well as investigate possible associations between LBP and workplace exposures. Information from 3530 employees in four mines was collected and analyzed in a cross- sectional study. One half of all employees had LBP, even two of three in several professions as for drivers of some types of heavy vehicles. The study describes characteristics of LBP symptoms (frequency, intensity, duration and radiation to the leg). Two of three reported working in cold conditions weekly, one half worked in wet clothes at least five hours during the week. One half performed heavy lifting. The adjusted association for LPB was significant for work with wet clothes (OR=1.82) and cold conditions (OR= 1.52). The adjusted association for LBP with radiation was significant for work with wet clothes (OR= 1.44 ), cold environment (OR= 1.49) and being past driver (OR=1.50). Heavy lifting was not associated with LBP. Driving underground trucks and trains were the only vehicles associated with LBP. The study also describes how the mine workers’ health and work conditions are assessed in Murmansk oblast, in particular for whole body vibration. The study is a part of a Norwegian-Russian cooperation in occupational health aiming to improve the working conditions and health for mine workers in the north. The study recommends focusing on vehicle ergonomics and improved clothing in order to promote better prevention of LBP. Gruvenæringen øker i nord, hvor de største gruvesamfunnene er i Nord Russland. Økt kunnskap om de ansattes helse og arbeidsforhold er viktig for bedre sikkerhet og forebygging av helseproblemer. Hensikten med studien var å beskrive ...